RESIPROKAL MENGGUNAKAN SIMPAI MEMPERBAIKI BELAJAR PASSING ATAS BOLA VOLI - Bangun, Sabaruddin Yunis (Journal of Sport Science and Education, 2017)
The purpose of this study was to determine whether through the implementation of reciprocal teaching style by using the media to improve learning outcomes loops passing over a volleyball student-SMP 40 Medan. The research method used is descriptive quantitative approach to the type of classroom action research. In this case the researchers used a descriptive statistical analysis. For example, to find the mean, percentage of student success. The results of this study is to use Media Reciprocal teaching style hoops give effect to the improvement of learning outcomes of students Passing the Volleyball Field SMPN 40 academic year 2015/2016. Value of the average percentage of students in the pre-test was 51% (Not Completed), the post-test I mean value increased to 56.83% of students (Not Completed), and the implementation of the post-test II the average student has reached 73.5% (Completed)